1994
DOI: 10.1159/000126741
|View full text |Cite
|
Sign up to set email alerts
|

Fast Glucocorticoid Feedback Inhibition of ACTH Secretion in the Ovariectomized Rat: Effect of Chronic Estrogen and Progesterone

Abstract: The purpose of this study was to determine whether estrogen and progesterone influence fast glucocorticoid negative feedback regulation of the ACTH and corticosterone (CORT) responses to stress. Mature rats were ovariectomized and 6 weeks later implanted with 17β-estradiol (E2,0.5 mg), E2 and progesterone (P, 100 mg; E2+P group) or placebo pellets (OVX). Seven days later rats were subjected to a single or repeated intermittent footshock stress (0.2 mA, 15 s duration, 0.5 s on).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 40 publications
5
62
1
3
Order By: Relevance
“…The effects of estradiol on cortisol secretion are complex. In ovariectomized animals, inhibition of HPA axis responses to stressors is seen with short-term, physiological levels of estradiol replacement (Redei et al, 1994;Young et al, 2001;Dayas et al, 2000;Komesaroff et al, 1998), while higher doses and longer treatment regimens enhance HPA axis reactivity to stressors (Burgess and Handa, 1992;Carey et al, 1995;Viau and Meaney, 1991). We observed a significant negative correlation between the increase in estradiol (but not testosterone) and the decrease in cortisol AUC from the hypogonadal to the testosterone replaced condition.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The effects of estradiol on cortisol secretion are complex. In ovariectomized animals, inhibition of HPA axis responses to stressors is seen with short-term, physiological levels of estradiol replacement (Redei et al, 1994;Young et al, 2001;Dayas et al, 2000;Komesaroff et al, 1998), while higher doses and longer treatment regimens enhance HPA axis reactivity to stressors (Burgess and Handa, 1992;Carey et al, 1995;Viau and Meaney, 1991). We observed a significant negative correlation between the increase in estradiol (but not testosterone) and the decrease in cortisol AUC from the hypogonadal to the testosterone replaced condition.…”
Section: Discussionmentioning
confidence: 58%
“…While both testosterone and estradiol modulate glucocorticoid receptor activity in brain regions mediating restraint of the HPA axis (Burgess and Handa, 1992;Carey et al, 1995;Redei et al, 1994;Peiffer et al, 1991), a more parsimonious explanation suggests that the blunted cortisol secretion during testosterone administration results in less restraint on ACTH secretion, consistent with the greatest difference in the cortisol : ACTH ratios between conditions occurring from 120 to 180 min. Similarly, a central action of testosterone or estradiol should appear as increased basal ACTH levels and would not be apparent with exogenous CRH stimulation (or would appear as blunting due to CRH receptor downregulation at the corticotroph).…”
Section: Discussionmentioning
confidence: 99%
“…Burgess and Handa (1992) used an estradiol implant, which produced constant levels of estradiol of 75 pg/ ml, which is a physiological dose, but delivered this dose for 21 days, which is much longer than the duration of estrogen exposure in the normal rat estrus cycle. In contrast, the study by Redei et al (1994) found a reduced HPA axis response to footshock stress in ovariectomized rats 7 days following implantation of estradiol pellets which produced blood levels in the physiological range (160 pg/ml). The results of the study by Redei et al (1994) are consistent with the results from our study, which also measured stress responses after 7 days of low dose estradiol replacement.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, the study by Redei et al (1994) found a reduced HPA axis response to footshock stress in ovariectomized rats 7 days following implantation of estradiol pellets which produced blood levels in the physiological range (160 pg/ml). The results of the study by Redei et al (1994) are consistent with the results from our study, which also measured stress responses after 7 days of low dose estradiol replacement. Blunting of the HPA axis response to stress has also been found during physiological dose estrogen replacement for longer periods in species with longer estrus cycles.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation